Program Pembiasaan Penguatan Pendidikan Karakter Terhadap Nilai Karakter Tanggung Jawab kepada Peserta Didik di SMK Negeri 1 Pacet Kabupaten Cianjur - Putri Rizki Anugrah Illahi; Delila Kania; Elan (UNIVERSITAS SERAMBI MEKKAH, 2024)
The Central Indonesian nation is experiencing a crisis of moral degradation, such as the rise of motorcycle gang t-shirts, brawls, acts of corruption in all walks of life, public lies, and a lack of legal certainty. The aim is to determine the attitudes generated by students in the character education habituation program towards the character value of responsibility. This research is a type of qualitative descriptive research carried out at SMK Negeri 1 Pacet, Cianjur Regency, with data collection techniques using in-depth interview methods through interview instruments, observation methods through observation instruments, and documentation methods. The strategy used by the school to familiarize students is to hold several activities, namely the red and white flag ceremony, morning assembly every Wednesday, and religious activities every Friday.